Identifying key factors affecting of the projects objectives in Baghdad Province by using experts interview technique - abd Al-jaleel, Halah (Anbar Journal of Engineering Sciences, 2022)
The performance of the construction industry is regarded as one of the most significant variables in the global economic development success of nations. As a result, it requires focusing on strengths to enhance them and weaknesses to address them. This study aims to identify the key factors affecting the objectives of construction projects. To achieve the study aim, previous records and documents of two completed projects were studied carefully to identify problems that occurred and the impact of these problems on the project objectives. After that, an experts’ interview was conducted to identify the key factors affecting the purposes of the construction project. The results of this study identified (33) key factors affecting the achievement of the construction project objectives, where the factor "The financial allocation for the project" was the most important, while the factor "Bad a health and safety plan in the project" was the least important.